Hubungan Tingkat Kecemasan Dengan Peningkatan Kadar Gula Darah Klien Diabetes Mellitus - Litae Litae; Maria Magdalena Purba; Irene Febriani Febriani (Husada Mahakam, 2019)
Diabetes Mellitus (DM) is a medical disorder is a collection of symptoms caused by elevated levels of sugar or due to insulin resistance. DM is a non-communicable diseases. Riskesdas 2007 in Central Kalimantan diabetes prevalence of 0.9%, but were diagnosed by health personnel by 0.6%. While in the city of Palangkaraya. Prevalence of diabetes of 1.4%, but were diagnosed DM client just as much as 1.1%. This study aims to determine the relationship of the level of anxiety with increased blood sugar levels in diabetes mellitus clients in the region of Bukit Pukesmas Hindu city of Palangkaraya. Methods descriptive analytic cross sectional study design. The research sample as many as 65 people. The results showed that the DM Client Anxiety in Puskesmas Bukit Hindu city of Palangkaraya that her blood sugar levels <200 mg / dl was 23.1% mild anxiety and 24.6% were worried. Anxiety DM client that blood glucose levels> 200 mg / dl was 21.5% mild anxiety, and 30.8% were worried. Obtained a significant relationship between the level of anxiety with increased levels of sugar in clients with diabetes mellitus, where respondents blood sugar> 200 mg / dl with a moderate level of anxiety has peluag 5.787 times greater risk than the volunteers were mild anxiety level.